Effect of wind speed on evaporation rate in air conditioner based desalination units - Ibnu Sulistiono; Dan Mugisidi; Nurkholid; Oktarina Heriyani (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Due to environmental changes, ensuring access to clean water is challenging for many regions. This study examines how wind speed influences seawater evaporation rates in a desalination system. Conducted indoors, the research varied wind speeds (0.6 m/s, 0.7 m/s, and 0.8 m/s) while maintaining a consistent temperature. A modified window Air Conditioner (AC) served as the evaporation unit, with its condenser immersed in water to utilize released heat, and its evaporator used as a condenser. Water temperature was maintained at 60-70°C. Results demonstrated a significant increase in evaporation rates with higher wind speeds. The strong correlation between experimental and theoretical results underscores wind speed as a critical factor in enhancing freshwater production efficiency from seawater. These insights inform the design of more effective desalination systems, offering potential solutions to water scarcity challenges in vulnerable regions